Recombineering Hunchback identifies two conserved domains required to maintain neuroblast competence and specify early-born neuronal identity - Tran, Khoa D. (Company of Biologists, 2010)
The Hunchback/Ikaros family of zinc-finger transcription factors is essential for specifying the anterior/posterior body axis in insects, the fate of early-born pioneer neurons in Drosophila, and for retinal and immune development in mammals. Hunchback/Ikaros proteins can directly activate or repress target gene transcription during early insect development, but their mode of action during neural development is unknown. Here, we use recombineering to generate a series of Hunchback domain deletion variants and assay their function during neurogenesis in the absence of endogenous Hunchback. Previous studies have shown that Hunchback can specify early-born neuronal identity and maintain ‘young’ neural progenitor (neuroblast) competence. We identify two conserved domains required for Hunchback-mediated transcriptional repression, and show that transcriptional repression is necessary and sufficient to induce early-born neuronal identity and maintain neuroblast competence. We identify pdm2 as a direct target gene that must be repressed to maintain competence, but show that additional genes must also be repressed. We propose that Hunchback maintains early neuroblast competence by silencing a suite of late-expressed genes.